My father's secret war : a memoir - Franks, Lucinda (New York : Miramax Books/Hyperion, 2007)
In this memoir, journalist Lucinda Franks describes her quest to learn to know her father. During World War II Thomas Franks served as spy in the Third Reich. In 1945 he was among the first soldiers into Ohrdruf, a subcamp of Buchenwald near the town of Gotha, Germany. As Tom's dementia progresses, Lucinda gathers fragments of his memories in order to understand her father and his secrets.
Keywords: Franks, Thomas Edward; Franks, Lucinda; World War, 1939-1945 -- Military intelligence -- United States; Spies -- United States -- Biography; Fathers and daughters -- United States